Candida–Bacterial Biofilms and Host–Microbe Interactions in Oral Diseases - Negrini, Thais de Cássia [UNESP]; Koo, Hyun; Arthur, Rodrigo Alex (Springer Nature, 2019)
Oral cavity harbors a complex and highly diverse microbial community. Cross-kingdom interactions between Candida and oral bacteria are critical for their co-existence, which may also affect the course and the severity of biofilm-mediated bacterial-mediated diseases. C. albicans has been found in polymicrobial biofilms associated with denture stomatitis, oral mucositis, dental caries, periodontal diseases, peri-implantitis, and root canal infection. Thus, it is of utmost importance to unravel the mechanisms of Candida–bacterial interactions and their impact on the onset and severity of cross-kingdom biofilm-related diseases. Here, we highlight the potential role of Candida–bacterial biofilm interactions in the pathogenesis of oral diseases, especially mucosal infections and dental caries. The influence of Candida–bacterial biofilms on the mucosal host immune response is also discussed. Finally, we present some of the current and prospective therapeutic strategies for controlling these cross-kingdom interactions and their virulence properties associated with oral diseases.